Estimation of Conditional Asset Pricing Models with Integrated Variables in the Beta Specification - Antonios Antypas; Guglielmo Maria Caporale; Nikolaos Kourogenis; Nikitas Pittis (Center for Economic Studies and ifo Institute (CESifo), 2019)
We introduce a methodology which deals with possibly integrated variables in the specification of the betas of conditional asset pricing models. In such a case, any model which is directly derived by a polynomial approximation of the functional form of the conditional beta will inherit a nonstationary right hand side. Our approach uses the cointegrating relationships between the integrated variables in order to maintain the stationarity of the right hand side of the estimated model, thus, avoiding the issues that arise in the case of an unbalanced regression. We present an example where our methodology is applied to the returns of funds-of-funds which are based on the Morningstar mutual fund ranking system. The results provide evidence that the residuals of possible cointegrating relationships between integrated variables in the specification of the conditional betas may reveal significant information concerning the dynamics of the betas.
Keywords: G10; G23; C10; 330; conditional CAPM; time-varying beta; cointegration; Morningstar star-rating system